PENGEMBANGAN KOGNITIF DAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN BERMAIN BALOK DI TAMAN KANAK-KANAK PLUS SWASTA DARUL ILMI MURNI MEDAN - Anita Yus; jamilah thahir (JURNAL TEMATIK, 2018)
This research aims to develop cognitive and creativity of group B through playing block activities in TK Plus Private Darul Ilmi Murni Medan. This research is a classroom action research (Class Room Action Research) it is a research done by teachers to improve the learning process. The study consists of four steps, namely: (a) planning (planning): (b) action (action): (c) observation (observing): (d) the reflection (reflecting). Based on the results of the above research can be concluded that through the activities of playing the beam can develop the cognitive and creativity of children in Kindergarten Plus Private Private Darul Ilmi Murni Medan.